Quitarse el peso de la historia: Isidoro Valcárcel Medina y su «2000 d. de J. C» - Estella Noriega, Ignacio (Tropelías: Review of Literary Theory and Comparative Literature, 2016)
Quitarse el peso de la historia: Isidoro Valcárcel Medina y su 2000 d. de J. C Este artículo propone una lectura de 2000 d. de J. C. (2001), uno de los trabajos más enigmáticos del Premio Nacional de Bellas Artes (2007) y Premio Velázquez (2015) Isidoro Valcárcel Medina. Cada una de las páginas del libro aborda un año en el devenir histórico hasta el año 2000; pero en vez de exponer los grandes eventos de la historia, se concentra en los hechos más banales y prácticamente anecdóticos que son narrados de forma tal que parecen rayar lo improbable. Los diferentes modelos historiográficos de contar la historia en los que se podría haber basado Medina y sus implicaciones, la economía del conocimiento, la actitud ante el pasado y el papel de la historia como constructora de la subjetividad nacional en la cultura española contemporánea, son analizados en el artículo para contextualizar esta obra de Medina. Palabras clave: arte contemporáneo, libros de artista, Isidoro Valcárcel Medina, 2000 d. de J. C., historiografía contemporánea, performance, políticas de la memoria y de la historia Lifting the burden of history: Isidoro Valcárcel Medina and his 2000 d. de J. C. This essay aims at contextualizing 2000 d. de J. C. (2001), one of the most intricate art-books by the awardee of both the Premio Nacional de Bellas Artes (2015) and the Velázquez (2007) art prizes, Isidoro Valcárcel Medina. Every page that composes this book contains what at first sight would appear to be a historical account on every year until 2000. A closer look shows that, in reality, the content of each page focuses on banal events, almost anecdotic acts that occurred on each year. Instead of using the prototypical historical discourse, the narrative style is always on the edge of falling into the unconceivable or even the inaccuracy. Different historiographical schools that might have influenced the artist and their implications, the economy of knowledge, the collective attitude towards the past and the history’s ideological product —building national subjectivity at least in Spain— will be the main areas of interest through which this essay will contextualize Medina’s work. Key words: contemporary art, artists’ books, Isidoro Valcárcel Medina, 2000 d. de J. C., contemporary historiography, performance, memory and history politics. Lifting the burden of history: Isidoro Valcárcel Medina and his «2.000 D. DE J.C» Abstract: This essay aims at contextualizing «2.000 d. de J.C.» (2001), one of the most intricate art-books by the awardee of both the Premio Nacional de Bellas Artes (2015) and the Velázquez (2007) art prizes, Isidoro Valcárcel Medina. Every page that composes this book contains what at first sight would appear to be a historical account on every year until 2000. A closer look shows that, in reality, the content of each page focuses on banal events, almost anecdotic acts that occurred on each year. Instead of using the prototypical historical discourse, the narrative style is always on the edge of falling into the unconceivable or even the inaccuracy. Different historiographical schools that might have influenced the artist and their implications, the economy of knowledge, the collective attitude towards the past and the history’s ideological product —building national subjectivity at least in Spain— will be the main areas of interest through which this essay will contextualize Medina’s work. Key words: contemporary art, artists’ books, Isidoro Valcárcel Medina, «2.000 d. de J.C.», contemporary historiography, performance, memory and history politics.